Metode Dakwah Rumah Tahfidz Nurul Fikri Kota Bengkulu Dalam Meningkatkan Hafalan Al-Qur’an - Abdi Zulkarnain Sitepu (JOISCOM (Journal of Islamic Communication), 2020)
ABSTRACT The memorizing of Al-Qur'an is a special gift ‘fadhal’ from Allah as an effort that we cannot attempt. Every Muslim is required to memorize of Al-Qur'an that will be used in praying activity. The formulation of this study is how the da'wah strategy at Nurul Fikri Tahfidz house of Bengkulu city for improving the quality of students’ memorizing. This study aims to determine the various obstacles and find out the da'wah strategy conducted in memorizing Al-quran by Nurul Fikri Tahfidz House. This research was conducted at Rumah Tahfidz Nurul Fikri from January to February 2019. The type of research was research field with qualitative approach that produces descriptive data in the form of written expressions obtained directly. This research reveals the phenomena that found in the field as a way in improving the memorization of students. The data collected through observation, interviews and documents. Based on the results study that the method of preaching as practiced at House of Tahfidz Nurul Fikri used al-Mau'idzah al-hasanah method or good lessons. There was no specific method so they do da'wah with all his personality. Giving good teaching becomes a role model or a good example for the students. As well as providing various facilities and services toward students. Moreover, showing the caring attitude, friendly, and friendly. Thus da’wah provide motivations to students when they were feel bored. The teachers who were the fosters the santri to recite hafidz Al-qur'an on 30 Juz, so that they can understand when there are problems in memorizing Al-quran. Keywords: Da'wah Method, Tahfidz House, Al-Qur'an Recitation.